The Use of Christopher Robin Movie to Improve Students Narrative Writing - Nandia Rosty; Muhamad Sofian Hadi; Mutiarani Mutiarani (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
The goal of this research was to proven that using Christopher Robin movie was effective to improve students narrative writing. In this era the English Language is very important, It is now becoming the most important language in the world. Almost all people from various countries around the world use it for communication, including schools that are continental Asia. There are four skills in English that every students have to mastery, there are: reading, listening, speaking, and writing. In this research focus on writing skill and the material is narrative text. This research has been conducted in Madrasah Aliyah Miftahul Umam. It used pre-experimental design that only used one experimental class that was contained 21 students in XII IPA, the data analyzed from quantitative method. To collected the data, this research used pre-test and post-test that given to the students. To improve students narrative writing, this research used Christopher Robin movie. That the students watched the movie after pre-test or before the post-test given. Movie will make students more interested and comfortable in learning to writing in a class. The results showed that the students mean pre-test was 61.52 and post-test mean was 89.80. t-score was obtained 18.025, and significant (2-tailed) was 0.00 lower that α = 0.05. Thus it can be said that the use Christopher Robin Movie to improve students narrative writing was effective.